2010
DOI: 10.1002/pssc.200983261
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of photoluminescence from P‐doped ZnMgTe bulk crystals of high quality grown by Bridgman method

Abstract: High quality P‐doped Zn1‐xMgx Te crystals with Mg composition x of 0.09 to 0.3 were grown by vertical Bridgman method. The typical value of the full width at half maximum of (004) X‐ray ricking curve was 65.7 arcsec. For the first time temperature dependence of photoluminescence measurement were successfully attained by using the P‐doped Zn1‐xMgx Te crystals. All the crystals showed not only excitonic emission with no donor‐acceptor pair emission at low temperature but also photoluminescence (PL) band originat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…It is found that resistivity tends to increase as Mg content increases while the carrier concentration tends to decrease. Such a decrease in carrier concentration may be partially due to an increase in the activation energy of P-acceptor by widening the band-gap with Mg content, which has also been revealed by the previous PL analyses [9].…”
Section: Methodsmentioning
confidence: 80%
See 4 more Smart Citations
“…It is found that resistivity tends to increase as Mg content increases while the carrier concentration tends to decrease. Such a decrease in carrier concentration may be partially due to an increase in the activation energy of P-acceptor by widening the band-gap with Mg content, which has also been revealed by the previous PL analyses [9].…”
Section: Methodsmentioning
confidence: 80%
“…The growth was carried out in almost the same manner as in the previous studies [2,8,9]. Briefly, Zn, Mg, Te and Zn 3 P 2 were used as source materials.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations